Dataset accompanying: Echolocation click parameters and biosonar behaviour of the dwarf sperm whale (Kogia sima) - Malinka, Chloe (Zenodo, 2020)
This dataset accompanies the manuscript "Echolocation click parameters and biosonar behaviour of the dwarf sperm whale ( Kogia sima )." All source parameters of on-axis clicks are available in MATLAB files, for both the deep water (n=46) and shallow harbour (n=870) datasets.The deep water dataset was collected using a 7-channel vertical hydrophone array in the Bahamas, and the shallow harbour dataset was collected using a single-channel recorder in South Africa. Metadeta explaining thevariables are found within the MATLAB files under 'Comments'. Details on data collection, curation and analysis can be found in the Malinka et al., Kogia publication (https://jeb.biologists.org/content/224/6/jeb240689). For comments/questions, please contact chloe.e.malinka [at] bio.au.dk Here is the publication that uses this dataset: Malinka, C. E., Tønnesen, P., Dunn, C. A., Claridge, D. E., Gridley, T., Elwen, S. H., & Teglberg Madsen, P. (2021). Echolocation click parameters and biosonar behaviour of the dwarf sperm whale (Kogia sima). The Journal of Experimental Biology, 224(6), jeb240689. doi:10.1242/jeb.240689.